Recent advances in cardio-oncology: a report from the 'Heart Failure Association 2019 and World Congress on Acute Heart Failure 2019' - Anker, Markus S; Hadzibegovic, Sara; Lena, Alessia; Belenkov, Yury; Bergler-Klein, Jutta; de Boer, Rudolf A; Farmakis, Dimitrios; von Haehling, Stephan; Iakobishvili, Zaza; Maack, Christoph; Pudil, Radek; Skouri, Hadi; et al. (ESC heart failure, 2019)
While anti-cancer therapies, including chemotherapy, immunotherapy, radiotherapy, and targeted therapy, are constantly advancing, cardiovascular toxicity has become a major challenge for cardiologists and oncologists. This has led to an increasing demand of cardio-oncology units in Europe and a growing interest of clinicians and researchers. The Heart Failure 2019 meeting of the Heart Failure Association of the European Society of Cardiology in Athens has therefore created a scientific programme that included four dedicated sessions on the topic along with several additional lectures. The major points that were discussed at the congress included the implementation and delivery of a cardio-oncology service, the collaboration among cardio-oncology experts, and the risk stratification, prevention, and early recognition of cardiotoxicity. Furthermore, sessions addressed the numerous different anti-cancer therapies associated with cardiotoxic effects and provided guidance on how to treat cancer patients who develop cardiovascular disease before, during, and after treatment.
Keywords: kardiologie; Cardiology; kardiotoxicita; Cancer; nádory; lidé; srdeční selhání; Neoplasms; Cardiotoxicity; Heart Failure; Heart failure; Humans